Cell‐free production of a therapeutic protein: Expression, purification, and characterization of recombinant streptokinase using a CHO lysate. Issue 1 (6th October 2017) - Tran, Kevin; Gurramkonda, Chandrasekhar; Cooper, Merideth A.; Pilli, Manohar; Taris, Joseph E.; Selock, Nicholas; Han, Tzu‐Chiang; Tolosa, Michael; Zuber, Adil; Peñalber‐Johnstone, Chariz; Dinkins, Christina; Pezeshk, Niloufar; et al.
Abstract: The use of cell‐free systems to produce recombinant proteins has grown rapidly over the past decade. In particular, cell‐free protein synthesis (CFPS) systems based on mammalian cells provide alternative methods for the production of many proteins, including those that contain disulfide bonds, glycosylation, and complex structures such as monoclonal antibodies. In the present study, we show robust production of turbo green fluorescent protein (tGFP) and streptokinase in a cell‐free system using instrumented mini‐bioreactors for highly reproducible protein production. We achieved recombinant protein production (∼600 μg/ml of tGFP and 500 μg/ml streptokinase) in 2.5 hr of expression time, comparable to previously reported yields for cell‐free protein expression. Also, we demonstrate the use of two different affinity tags for product capture and compare those to a tag‐free self‐cleaving intein capture technology. The intein purification method provided a product recovery of 86%, compared with 52% for conventionally tagged proteins, while resulting in a 30% increase in total units of activity of purified recombinant streptokinase compared with conventionally tagged proteins. These promising beneficial features combined with the intein technology makes feasible the development of dose‐level production of therapeutic proteins at the point‐of‐care. Abstract : In the present study, a cell‐free protein synthesis was explored to produce recombinant streptokinase using CHO lysate. Two different affinity tags were used for protein capture and compared to a tag‐free self‐cleaving intein capture technology. The intein purification method provided greater product recovery and activity compared with conventionally tagged proteins. Cell‐free protein synthesis combined with the intein technology makes feasible the rapid production of dose‐level production of therapeutic proteins at the point‐of‐care.